The Flying Ash Taken by Wet Process from C.E.T. Holboca Iassy – Major Pollution Source. (2016) - Ioniuc, Ileana; Diaconu, Livia Ingrid; Grigorescu, Cristina; Mihaela, Alexoaie Monica
Abstract: The study is underlining the negative effects and is proposing some solutions of reintroduction into the economic circuit of this type of material aiming to reduce the depositing dumps volume. In the study were analyzed that some affections that are observed on children and adults due to the presence in the inhaled air of the power plants ashes from dumps. Also ashes chemical and mineralogical composition and some specific properties of dusty materials were presented.